Peranan Komisi Pengawas Persaiangan Usaha (KPPU) Dalam Menegakan UndangUndang Nomor 5 Tahun 1999 Tentang Larangan Praktek Monopoli Dan Persaingan Usaha Tidak Sehat - Rosdalina Bukido; Laila F Bamatraf (IAIN Manado, 2017)
Law No. 5 of 1999 concerning the prohibition of monopolistic practices and unfair business competition is established to prevent unfair business competition in Indonesia based on the centralization of economic power on individuals or certain groups either in the form of monopoly in spite of other forms of unfair business competition before the law is applied. Therefore, this research is brought out to declare the function and role of KPPU itself to combat various kinds of monopolistic practices and unfair business competition that is emerging in society.